KONDISI SOSIAL EKONOMI PENAMBANG PASIR DI KEJORONGAN PETOK KECAMATAN PANTI KABUPATEN PASAMAN - Riza, Nova - (STKIP PGRI Sumbar, 2014)
The purpose of this research is to know the economic social of sand miners in Petok Kejorongan, Panti Subdistrict, Pasaman Regency. The type of this research is descriptive. The population of this research of all of sand miners in Petok Kejorongan, Panti Subdistrick, Pasaman Regency that consist of three location. The sample ofrepondense is taking with total sampling technique with 55 sample. The data analysis technique is using persentase analysis with formulas and after that us likers scale the data collection technique through questionnaires or instrument. The result of reseacrh and that: 1) Condition basic needs sand miners in Petok Kejorongan, Panti Subsdistrict, Pasaman Regency looked from nothing condition, is generaly solden to buy cloth in a month with 49.09% percentage, food condition is enough to fulfil daily need with 72.73% percentage and board condition (housing) is generally semi permanent and finish about 100% noth 30.91% percentage. 2) incoming condition of sand miners in Petok Kejorongan, Panti Subdistrict, Pasaman regency is generally Rp.2,000,000.- with 32.73% percentage the soarces of income is generally from husband and wife with 52.73% percentage. 3) Education condition of sand miners in Petok Kejorongan, Panti Subdistrict Pasaman Regency with likert scale 53.36% percentage is in enough criteria. 4) Health condition of sand miners in Petok Kejorongan, Panti Subdistrict, Pasaman Regency with likert scale 56.66% percentage is in enough criteria. 5) Of live food side line condition of sand miners in Petok Kejorongan, Panti Subdistrict, Pasaman Regency is generally present with 38.18% percentage. The bind of second job is farming with 52.72% percentage with out coming side in a week about Rp.100,000 with 43.63% percentage.